A completeness indicator of gestational and congenital syphilis information in Brazil - Guilherme Lopes de Oliveira; Andrêa JF Ferreira; José Guilherme Santana; Raquel Martins Lana; Andrey Moreira Cardoso; Carlos Teles; Rosemeire L. Fiaccone; Rosana Aquino; Maria Auxiliadora Santos Soares; Enny S. Paixao; Idália Oliveira Santos; Leonardo Salvi; et al. (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To evaluate the quality of information on gestational syphilis (GS) and congenital syphilis (CS) on the Sistema de Informação de Agravos de Notificação (SINAN-Syphilis Brazil - Notifiable Diseases Information System) by compiling and validating completeness indicators between 2007 and 2018. METHODS Overall, care, and socioeconomic completeness scores were compiled based on selected variables, by using ad hoc weights assigned by experts. The completeness scores were analysed, considering the region and area of residence, the pregnant woman's race/colour, and the year of case notification. Pearson's correlation coefficients were used to validate the scores obtained by the weighted average method, compared with the values obtained by principal component analysis (PCA). RESULTS Most selected variables presented a good or excellent degree of completeness for GS and CS, except for clinical classification, pregnant woman's level of education, partner's treatment, and child's race/colour, which were classified as poor or very poor. The overall (89.93% versus 89.69%) and socioeconomic (88.71% versus 88.24%) completeness scores for GS and CS, respectively, were classified as regular, whereas the care score (GS-90.88%, and CS-90.72%) was good, despite improvements over time. Differences in the overall, care and socioeconomic completeness scores according to region, area of residence, and ethnic-racial groups were reported for syphilis notifications. The completeness scores estimated by the weighted average method and PCA showed a strong linear correlation (> 0.90). CONCLUSION The completeness of GS and CS notifications has been improving in recent years, highlighting the variables that form the care score, compared with the socioeconomic scores, despite differences between regions, area of residence, and ethnic-racial groups. The weighted average was a viable methodological alternative easily operationalised to estimate data completeness scores, allowing routine monitoring of the completeness of gestational and congenital syphilis records.